2001
DOI: 10.1038/sj.mp.4000879
|View full text |Cite
|
Sign up to set email alerts
|

Common effects of chronically administered antipanic drugs on brainstem GABAA receptor subunit gene expression

Abstract: Panic disorder is an anxiety disorder that can be treated by long-term administration of tricyclic antidepressants such as imipramine, monoamine oxidase inhibitors such as phenelzine, or the selective serotonin reuptake inhibitor (SSRI) antidepressants. Clinical data also indicate that some benzodiazepines, such as alprazolam, are effective antipanic agents, and that their therapeutic onset is faster than that of antidepressants. Benzodiazepines are well known for their action at GABA A receptors, and preclini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…In contrast, chronic antidepressants upregulated a1, a3, b1, b2, and g2 genes in rat brainstem [Tanay et al, 1996[Tanay et al, , 2001, while altered anxiety and depression-related behavior was found in mutant mice lacking B1 and B2 receptors [Mombereau et al, , 2005. A recent human study showed that severe treatment-resistant depression with anxiety was linked to a mutation in the b1 subunit of GABA-A receptor [Kosel et al, 2004].…”
Section: Genetic Data: Gabaergic Receptorsmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast, chronic antidepressants upregulated a1, a3, b1, b2, and g2 genes in rat brainstem [Tanay et al, 1996[Tanay et al, , 2001, while altered anxiety and depression-related behavior was found in mutant mice lacking B1 and B2 receptors [Mombereau et al, , 2005. A recent human study showed that severe treatment-resistant depression with anxiety was linked to a mutation in the b1 subunit of GABA-A receptor [Kosel et al, 2004].…”
Section: Genetic Data: Gabaergic Receptorsmentioning
confidence: 81%
“…Elevated cortical GABA after AD treatment in rats [Yang and Shen, 2005]. Increased brainstem GABA-A a1, a3, b1, b2 and g2 subunits mRNA levels [Tanay et al, 1996[Tanay et al, , 2001] and hippocampal GABA-B1 expression [Sands et al, 2004] after chronic AD treatment in rats. Increased Cl À uptake in submissive rats after AD treatment [Malatynska et al, 1995[Malatynska et al, , 2000.…”
Section: Historical Background and Recent Findingsmentioning
confidence: 99%
“…Long-term treatment with abecarnil, diazepam, imidazenil, and zolpidem in vivo had no effect on ␣2 mRNA expression in any brain region quantified Holt et al, 1996;Impagnatiello et al, 1996) (Table 2). Long-term treatment with alprazolam up-regulated ␣2 mRNA in the brainstem by 76% (Tanay et al, 2001). Of all brain regions studied, the caudateputamen was the only one in which flurazepam downregulated ␣2 mRNA (Tietz et al, 1999a).…”
Section: A Benzodiazepinesmentioning
confidence: 99%
“…Holt et al, 1996Holt et al, , 1997a, with the exception of diazepam given as daily injections (Arnot et al, 2001). Long-term alprazolam had no effect on ␤3 mRNA expression in the brainstem (Tanay et al, 2001). Withdrawal from flurazepam for 2 days downregulated ␤3 mRNA expression in all hippocampal subregions (Tietz et al, 1993(Tietz et al, , 1999a (Table 5).…”
Section: A Benzodiazepinesmentioning
confidence: 99%
See 1 more Smart Citation